Using Multiple Linear Regression Model to Identify the Relationship between Leadership Styles and Job Satisfaction in Government Organizations in Sulaimani City - KRG - Nozad H.Mahmood; Sharoo N. Fadhil; Nawroz F. Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The intent of the study was to examine the impact of managers’ leadership styles on employee job satisfaction of the government organizations in Sulaimani city. The study’s sample consists of (398) employees that will help answering the study’s questions and hypotheses; in addition, a questionnaire developed for the detection of leadership style features (Autocratic leadership style, Democratic leadership style, and Laissez-Faire leadership style) and the level of Employees Job Satisfaction on the authority of each leadership style. The most important findings and conclusions of the research are: The correlation between Employees Job Satisfaction and both (Autocratic and Democratic) leadership styles are in moderate level and towards a positive direction. In other words, Employees Job Satisfaction increases as Autocratic or Democratic leadership styles increases in an organization. Furthermore, Regression results indicates that there is statistically significant effect for Autocratic and Democratic leadership styles on Employees Job Satisfaction. Furthermore, Democratic leadership style influence came first regarding the level of the effect. Whereas, Laissez-Faire leadership style does not have any effect on the Employees Job Satisfaction. Based on the outcomes of this research, democratic leadership style is the greatest impact compared to others with regards to job satisfaction. In order to preside over their employees in daily activities and succeed in achieving the organizational goals, it is suggested that the powerful leader ought to have the high capability to control and identify at all levels of the organization. Furthermore, since the Laissez-Faire leadership style statistically was not significant according to the results, in order to increase employees job satisfaction in the government organization, the managers should get rid of this kind of leadership style in the public sectors or government organizations. Keywords: Multiple Linear Regression, Correlation Coefficient, Test Normality, Leadership Style, Autocratic Leadership Style, Democratic Leadership Style, Laissez-Faire Leadership Style, Employee Job Satisfaction.